PENGARUH PENERAPAN METODE MEMBACA TERBIMBING DALAM MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN PESERTA DIDIK KELAS IV SDN CENTRE MAWANG KAB. GOWA - Sarneti; St. Syamsudduha; Patiung, Dahlia; Halimah, Andi (Prodi PGMI IAI Sahid, 2025)
This thesis aims to testing the effect of applying the guided reading method in improving the reading comprehension skills of class IV students at SDN Center Mawang Kab. Gowa. This research is quantitative research, with a quasi experimental research design (quasi experimental design). The results of the analysis show that the reading comprehension skills of students who do not apply the guided reading method are in the high category, with an average pretest score of 61 and an average posttest score of 77. Meanwhile, the reading comprehension skills of students who apply the guided reading method are at high category, with an average pretest score of 59 and an average posttest score of 82. Then the results descriptive analysis show that the application of the guided reading method has a positive effect on the reading comprehension skills of class IV students at SDN Center Mawang Kab. Gowa. With a correlation value of 55.4%, the remaining 44.6% is influenced by other variables in the medium category.